Study of the relationship between health symptom reporting and mold measurements in First Nations housing - Allain, Erik (2008)
Study conducted in the First Nations community of Neskantaga in Northern - Northwestern Ontario, in the District of Kenora. The purpose of the study is to examine the relationship between health symptom reporting and mold concentration in First Nations housing. Indoor air quality is increasingly becoming a topic of concern for many homeowners, and the information on the issue is often controversial and misunderstood. Various studies report that a range of health symptoms are associated with being exposed to mold in the indoor environment, but there is still debate over which symptoms are included in this association and the amount of mold to which an individual must be exposed before the symptoms occur. One study concludes that, while there is general agreement that visible mold in the indoor environment is unhealthy and is a situation that must be corrected, the point at which mold contamination becomes a health concern is not known (Robbins et al., 2000). Other studies state that people experiencing mold-related health effects have diverse characteristics, and that, as there are currently no health-based exposure standards for molds, it is difficult, if not impossible, to predict who will experience symptoms and when (Bobbit et al., 2005; Rao et al., 1996). Even though these studies have led to a significant amount of scientific literature, unanimous agreement has not been reached as yet on whether or not mold in fact causes health symptoms in the individuals exposed. This subject is important, considering that it is reported that Canadians spend up to 70% of their time indoors—perhaps even more in the coldest months of the year (la). Therefore, when houses are contaminated with mold, the exposure time of the occupants is significant and ongoing. Housing inequalities among individuals living on and off reserve have also been recognized for some time. According to a report produced by the National Aboriginal Health Organization (RHS, 2002/03), nearly half (49%) of families living in band-owned houses report mold in their homes. This was confirmed in the 2003 Report ofthe Auditor General of Canada (RAGC, 2003), which stated: “Mold contaminates almost half of First Nations households.” First Nations homes are also about four times more likely to require extensive repairs than are Canadian homes overall (34% vs. 8%) (RHS, 2002/03). Exacerbating the problem is the fact that First Nations members live in homes that are, on average, nearly twice as crowded as Canadian homes overall (4.8 vs. 2.6 persons per room) (RHS, 2002/03). There are significant gaps in the literature regarding the health effects of mold on First Nations individuals. Very few studies have been conducted in which First Nations people were the target population and in which mold measurements and reported health symptoms were collected in a systematic fashion. This study was designed to bridge this gap by examining the association between reported health symptoms and mold concentration in an entire First Nations community.